Ein Leben wie in den Alpen? Tiroler Siedler und Siedlerinnen im Dschungel von Peru - Karin Zbinden Gysin (Revue de Géographie Alpine)
The paper shows how an ethnic group in Pozuzo, an ancient colony, composed of Tyrolean and German settlers in the Peruvian jungle, re-create an alpine way of life. Evidence from the field in Pozuzo and Tyrol is used as a case study to illustrate how cultural resources linked to ‘alpine’ ways of life are constructed and claimed within the multi-ethnic rural community of Pozuzo as well as within Tyrolean NGOs.